IMPLEMENTASI PEMBELAJARAN SYAWIR (DISKUSI) DALAM MENINGKATKAN PEMAHAMAN SANTRI PADA PELAJARAN FIQIH DI PONDOK PESANTREN MIFTAHUL HUDA GADING KOTA MALANG - Mohammad Syamsud Dhuha; Anwar Sa’dullah; Dian Mohammad Hakim (VICRATINA, 2021)
The research in this thesis is motivated by the fact that the times are constantly modern, and the world of education is required to continue to create innovative learning methods that are in accordance with the academic development of education. Responding to this, the miftahul huda gading Islamic Boarding School maintains the old method but is considered still relevant to the current situation, namely learning syawir (discussion). The use of this learning is a method that requires students to continue to learn and be active in teaching and learning activities so that later they can improve the critical pattern of students and so that the communication that is built between teachers and students is not only in one direction. Although it is a method that has existed for a long time, this syawir is considered effective in increasing the understanding of the students, especially in learning fiqh. The research focus of this paper is on how to plan poetry learning, implementation of poetry, and the obstacles that arise from the implementation of this verse, and to achieve this, the research was carried out with the type of qualitative research, where the data collection procedure was carried out through the methods of observation, interviews, and documentation.